Terra Territory: Reports on Collaboration Processes in Latin America - Rosenthal, Dália (Revista do Colóquio, 2023)
This article presents a reflective report on four series of works, “Diário de um Desaparecido”, “Chispa”, “Oro Sucio” and “Otros Territorios”, carried out between 2017 and 2019. The series act as a group of processes of creation and collaboration developed in artistic residencies and exhibitions in the territorial contexts of the Colombian Caribbean, northeastern Brazil and southern Cuba. This is a set of artistic works that brings, as its main element, the confrontation between perceptions about the territory and the land, mediated by the body and the landscape, through an equally dialogical perspective between culture and nature in contemporary times.